Racism in the novel “Dear Martin” by Nic Stone based on the perspective of W.E.B. Du Bois - Basid, Abdul; Syahril, Muhamad; Zawawi, Moh; Masrokhin (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Racist behavior to this day still occurs frequently in various parts of the world. Racist behavior appears no longer caused by differences in physical form, but has penetrated into differences in ideology to beliefs. This study aims to describe the forms of racist behavior in the novel “Dear Martin” by Nic Stone using W.E.B Du Bois’ racial theory. This study also reveals the factors affecting the emergence of racist act and understands the impact of racist act to the victims. The type of this study is descriptive qualitative study. The techniques of data validation use reading techniques and note-taking techniques, whereas the techniques of data validation use increasing persistence, triangulation, and discussion. This study shows that white people often carry out racism against black people in the United States. Racist behavior occurred in the form of undervaluing black co-workers, insulting black women, unfairly applying the law, and doubting the abilities of black students. Racist behavior arises because of differences in class and social status, differences in skin color, accusations of being the perpetrator of a crime, and allegations of affirmative action. Racist behavior has significant impact toward victims among individual, family, and society, such as loss of fighting spirit, trauma, considering all people from the majority race to be racist perpetrators, worrying about the safety of their families, growing feelings of hatred and revenge, and retaliating against behavior. Based on the results of these studies, the finding of this study is racist behavior tends to occur because someone thinks that he or his group is superior to others. Racist behavior can be minimized if every individual, family, community, and even the government implements the values ​​of equality and upholds human values ​​from an early age.